The Implementation of Virtual Learning in Vocational Subjects at SMP Negeri 17 Banda Aceh - Rosmala Dewi; Fitriana Fitriana; Rifqi Akmal; Nailul Muna (Universitas Serambi Mekkah, 2021)
This study aims to find out student learning outcomes in taking virtual learning and to find out the obstacles faced by teachers and students in Soft Material Craft Vocational Subjects during the virtual learning process. The method used in this research is qualitative with the technique of selecting subjects by purposive sampling. The research subjects were 5 people consisting of 1 teacher and 4 variedachieved students who were proved to have the highest score, lowest score, and those who missed assignment submissions. Data were collected through observation, interviews, and documentation. The results showed that the virtual learning results obtained by four students were different, some were very good at mastering soft material Vocational Subject, some were average, and some were poor. The obstacles faced by students were difficulties in absorbing learning subjects, weak internet networks and links that were sometimes difficult to access. While the obstacles faced by the teacher are difficulties in controlling and guiding students, especially when collecting assignments from the students. It is suggested that there is a cooperation between teachers and parents in instilling moral values, attitudes, and character during the virtual learning process.Keywords: The Implementation, Virtual Learning, Vocational Subjects.